PENGARUH MODERNISASI SISTEM INFORMASI PERPAJAKAN BERBASIS e-FAKTUR TERHADAP PENERIMAAN PPN (Studi Kasus Pada KPP Madya Jakarta Pusat) - Kartika Kartika; Vika Aryanto (STIE Mandala Jember, 2017)
This study aims to determine the effect of the Modernization of Tax Information System Based on e-Invoice to PPN Receipts. This research was conducted in KPP Madya Jakarta Pusat. The data used primary and secondary data. Data analysis used simple regression analysis. The result of the research shows that there is a positive and significant effect of of the Modernization of Tax Information System Based on e-Invoice to PPN Receipts in KPP Madya Jakarta Pusat.